Derivation of a Look-Up Table for Trans-Critical Heat Transfer in Water-Cooled Tubes - Zahlan, Hussam Ali Mustafa (Université d'Ottawa / University of Ottawa, 2015)
This thesis describes the development and validation of a look-up table capable of predicting heat transfer to water flowing vertically upward in a circular tube in the trans-critical pressure range from 19 to 30 MPa. The table was based on an extensive and screened experimental database and its trends were smoothened to remove unrealistic scatter and physically implausible discontinuities. When compared to other prediction methods, the present look-up table approximated the experimental data closer in values and trends. Moreover, unlike existing prediction methods, the table applies not only to normal heat transfer conditions but also to conditions with heat transfer deterioration and enhancement. A separate multi-fluid look-up table for trans-critical heat transfer was also developed, which besides the existing water database incorporated new measurements in carbon dioxide; the latter were collected at the University of Ottawa supercritical flow loop under conditions of interest for the current Super-Critical Water-Cooled Reactor designs, for which few water data were available in the literature. Existing fluid-to-fluid scaling laws were tested and two additional sets of scaling laws were proposed, which are applicable not only to the supercritical pressure region, but also to the high pressure subcritical region. The multi-fluid table is applicable to water at conditions of normal and abnormal heat transfer, but its applicability to model fluids is restricted to the normal heat transfer mode.
Keywords: Supercritical; Heat transfer; Fluid-to-fluid scaling; Look-up table; Experiment; Data; Near-critical pressure; Normal heat transfer; Deteriorated heat transfer